Same-sex Couples in Children’s Picture Books in French and in English: Censorship Somewhere Over the Rainbow? - Tarif, Julie (Meta, 2018)
This paper focuses on children’s picture books featuring same-sex couples in Anglophone and Francophone cultures, and more particularly in France and in the United States, with a particular interest in the censorship of these works. Censoring a book is common in the United States. This essay is a reflexion on the publication and reception of Francophone picture books on the topic – originals and translations. In this perspective, it also considers the question of the circulation of these books between the two cultures, as well as towards the two cultures respectively, Francophone picture books tending to be bolder in content than their Anglophone counterparts. Some references used to explain reception are gathered thanks to primary sources, in particular personal communications; others come from secondary sources, such as academic publications, blogs, and newspaper articles. This paper also explores the different forms of censorship, including the translation of a work from another culture or the alterations to the illustrations of an original work in an adaptation. The contrastive approach adopted reveals that, despite the growing number of picture books featuring same-sex couples, censorship is not only an American reality but a French reality as well.